2022
DOI: 10.3390/rs14030500
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal Set of Indicators for the Assessment of Flexible Pavement Stiffness from Deflection Monitoring: Theoretical Formalism and Numerical Study

Abstract: The monitoring of pavements along roads is generally based on the use of indicators directly derived from measurements. More specifically, the bearing capacity of pavements is often simply deduced from either the maximum deflection value measured or the difference between two measured values along the deflection basin. This paper proposes a methodology to define a set of orthogonal indicators adapted to the structure being evaluated. This methodology is presented for deflection measurements recorded on a flexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…So, in order to monitor the evolution of these characteristics during the pavement service life over time, a synthetic indicator that represents one of the pavement’s characteristics is calculated from a complete signal. This section proposes a concise presentation of the principle of this method, based on the calculation of derivatives and integrals; more details can be found in the study published by Simonin et al [ 12 ]. In this paper, the mathematical expressions were written with the hypothesis of summation over the repeated indices.…”
Section: Theoretical Background Of the Optimized Indicators Methods (...mentioning
confidence: 99%
See 1 more Smart Citation
“…So, in order to monitor the evolution of these characteristics during the pavement service life over time, a synthetic indicator that represents one of the pavement’s characteristics is calculated from a complete signal. This section proposes a concise presentation of the principle of this method, based on the calculation of derivatives and integrals; more details can be found in the study published by Simonin et al [ 12 ]. In this paper, the mathematical expressions were written with the hypothesis of summation over the repeated indices.…”
Section: Theoretical Background Of the Optimized Indicators Methods (...mentioning
confidence: 99%
“…This method, referenced as Optimized Indicators Method (OIM), was successfully applied for the processing of FWD signals by Simonin et al [ 12 ], and showed that the OIM makes it possible to evaluate separately the physical characteristics of the different layers of a pavement. In this case, the construction of the weighting functions with the OIM consists of identifying, in the first step, an analytical model that simulates the ND method’s signal by considering the physical characteristics of the studied structure.…”
Section: Introductionmentioning
confidence: 99%
“…As constructed, these weighting functions are sensitive to the variation of a specific characteristic of the pavement structure (modules or thicknesses of the layers, interface status, etc. ), as long as it remains in the linear domain and without being sensitive to the others parameters [3]. So, in order to monitor the evolution of this characteristic during the pavement service life over time, a synthetic indicator that represents one of the pavement characteristics is calculated from a complete signal.…”
Section: Theory Of the Optimized Indicators Methodsmentioning
confidence: 99%
“…The deflectometers are among the most current NDT method to characterize the structural state of pavements, therefore, it can be difficult to detect a defect that merges in the base layer to prevent its propagation through the bituminous layer, or vice versa. To overcome this limitation, the French "Laboratoire Auscultation, Modélisation et Expérimentation des infraStructures de transport" (LAMES) has developed an original method mentioned as Optimized Indicators Method (OIM) [3].…”
Section: Introductionmentioning
confidence: 99%